Literacy-Based Blended Learning in Early Childhood Education in the New Normal Era - Hermawan, Risdianto; Amalia, Dike; Aerin, Wafa (International Proceedings of Nusantara Raya, 2022)
Learning in early childhood education institutions during the pandemic generally encounters many obstacles and obstacles. One of the efforts made to overcome these obstacles is through blended learning. Using a blended learning model by combining online learning and face-to-face learning during the Covid-19 pandemic can increase the effectiveness of learning and the enthusiasm for learning of students because in addition to getting online learning materials, they also still receive direct assistance from teachers in the teaching and learning process by observing strict health protocols. This research is a qualitative descriptive research because it produces qualitative data. Data collection using interview, observation and documentation models. Analysis techniques using description techniques with the analysis model of Miles and Huberman's interaction with the flow include data collection, data reduction, data presentation and conclusions. The results of the study were concluded, first, literacy-based blended learning planning applied in wadas kelir playgroup includes preparing a Learning Implementation Plan (RPP) and preparing blended learning supporting facilities and infrastructure. Literacy-based blended learning in wadas kelir playgroups during this pandemic is carried out with the provision of one day of online learning and one day of offline learning with a maximum capacity of 10 students per class with a duration of 30 minutes every meeting hour. The learning evaluation system includes Self Assessment questions, Video Calls, and home visits that have been planned by teachers using various media.